1998
DOI: 10.1021/bi9813577
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Binding to the Peripheral Site of Acetylcholinesterase Initiates Enzymatic Catalysis. Substrate Inhibition Arises as a Secondary Effect

Abstract: Two sites of ligand interaction in acetylcholinesterase (AChE) were first demonstrated in ligand binding studies and later confirmed by crystallography, site-specific mutagenesis, and molecular modeling: an acylation site at the base of the active site gorge and a peripheral site at its mouth. We recently introduced a steric blockade model which demonstrated how small peripheral site ligands such as propidium may inhibit substrate hydrolysis [Szegletes, T., Mallender, W. D., and Rosenberry, T. L. (1998) Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
166
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 38 publications
11
166
2
Order By: Relevance
“…Unexpectedly, the crystal structure of the Torpedo californica enzyme (TcAChE) showed that the active site catalytic Ser-His-Glu triad is found at the bottom of a 20-Å deep gorge lined mostly with aromatic residues (5). The structure also revealed the nature and the location of the previously described peripheral and "anionic" sites; the former, located at the outer rim of the gorge, has been postulated to be the initial substrate binding site (6). The binding of ligand to this site has been proposed to slow down the traffic of substrate and product at the acylation site (6,7).…”
mentioning
confidence: 86%
“…Unexpectedly, the crystal structure of the Torpedo californica enzyme (TcAChE) showed that the active site catalytic Ser-His-Glu triad is found at the bottom of a 20-Å deep gorge lined mostly with aromatic residues (5). The structure also revealed the nature and the location of the previously described peripheral and "anionic" sites; the former, located at the outer rim of the gorge, has been postulated to be the initial substrate binding site (6). The binding of ligand to this site has been proposed to slow down the traffic of substrate and product at the acylation site (6,7).…”
mentioning
confidence: 86%
“…Substrate inhibition has been studied in other enzymes (20,(35)(36)(37), and its analysis can be complex (32,38,39). We observed that the R182A data are best explained by cooperative substrate inhibition (Equation 1).…”
Section: Cavity Depth As a Determinant Of Product Formation-thementioning
confidence: 99%
“…Assay solutions included 0.33 mM 5,5Ј-dithiobis(2-nitrobenzoic acid), and hydrolysis was monitored by formation of the thiolate dianion 3-carboxy-4-nitrothiophenol at 412 nm (⌬⑀ 412 nm ϭ 14.15 mM Ϫ1 cm Ϫ1 (29)). Hydrolysis rates v were measured at various substrate concentrations [S] in 20 mM sodium phosphate, 0.02% Triton X-100 (pH 7.0) at 25°C, and constant ionic strength was maintained with 0 -60 mM NaCl (14). …”
Section: -[N ␥ -(␤-Mts-propionyl)-␥-aminopropylamino]acridine (Iv)mentioning
confidence: 99%
“…The peripheral site (P-site) consists of a binding pocket near the surface of the enzyme at the mouth of the gorge and specifically binds certain ligands like the neurotoxin fasciculin (8 -11) and the fluorescent probes propidium (12) and thioflavin T (13). We have recently shown that catalysis is accelerated because cationic substrates transiently bind to the P-site en route to the A-site (14,15). However, ligand binding to the P-site also can inhibit AChE through a process we have called steric blockade (15,16).…”
mentioning
confidence: 99%